Integrated modelling of whole-plant metabolism and growth - Konuntakiet, T (2020)
Source-sink interactions describe the relationship between different plant organs and the division of labour in relation to source activity (resource uptake and assimilation) and sink activity (resource utilisation). Recently, multiscale growth models have been proposed as a tool to investigate unresolved aspects of whole-plant level processes, including source-sink interactions. In particular, constraint-based modelling using stoichiometric biochemical models has been shown to generate accurate predictions of metabolic fluxes and fine-grained, quantitative descriptions of plant biochemistry. The aim of this work was to develop a computational framework that captures the interactions between different organs during plant growth and the metabolic activity of each organ.